Enhancing the Success of Organizational Change : Exploring Middle Managers’ Different Roles During the Change Processes - Lindholm, Verneri (My University, 2021)
The increasing rate of change is widely recognized in today’s dynamic business environment. Changes occur more frequently than ever before, and companies are forced to adapt to them by reforming their organizational structures and operating models. In recent years, middle managers’ role and responsibilities have grown as a teamwork design has gained popularity within the organizations. The role of middle management is highly cross-functional as they hold a strategic location between organization’s top management and frontline employees. They balance between organization’s strategy and day-to-day activities, and hence, are also responsible for implementing changes. Due to the middle management’s essential yet poorly understood role in change processes, additional research on how differences in middle managers’ change practices and policies influence on organizational performance and improvement efforts’ success is needed. Hence, the aim of the thesis is to figure out how do middle managers influence on the organizational change processes. The theoretical framework of the study is formed by defining organizational change and different approaches to it, presenting and analysing existing frameworks and change management models, identifying different phases of a change process, and finally examining middle managers different roles, areas of responsibilities, and objectives during an organizational change process. As the study aims to fill the identified gap between the theory and practice, an empirical research is conducted. Qualitative research material is collected by interviewing people in middle management positions through semi-structured theme interviews. Findings of the empirical research are analysed and reflected to the theoretical framework of the study. Both theoretical and empirical findings of the study suggest that the middle managers’ role in organizational change processes is emphasized especially during the change implementation phase. Through change-oriented leadership, they can enhance the success of change processes and lead the organization into the desired direction. With their own actions, middle managers can also prevent possible change resistance, motivate people to engage in the change, and ensure continuity of the development. As theoretical contributions, this study seeks to provide academics new insights on today’s change management practices and how successful change leaders act during the change processes. In addition, the findings of the study reinforce the existing literature of the field and contribute to the prior studies in various ways.

Alati kasvava muutosnopeus on laajalti tunnistettu ilmiö nykypäivän dynaamisessa liiketoimintaympäristössä. Muutoksia tapahtuu useammin kuin koskaan aikaisemmin, ja yritysten on pakko sopeutua niihin uudistammalla organisaatiorakenteitaan ja toimintamallejaan. Viime vuosina sekä keskijohdon rooli että vastuualueet ovat kasvaneet, kun tiimityöskentelyn suosio on lisääntynyt yrityksissä. Keskijohdon rooli on erittäin monialainen, koska heillä on strateginen asema organisaation ylimmän johdon ja etulinjan työntekijöiden välillä. He tasapainottelevat organisaation strategian ja päivittäisen operatiivisen toiminnan välillä ja ovat näin ollen usein myös vastuussa uusien muutosaloitteiden jalkauttamisesta käytännöntasolle. Keskijohdolla on merkittävä – mutta silti heikosti ymmärretty rooli yritysten muutosprosessien aikana. Tarvitaan siis lisätutkimusta siitä, miten eroavaisuudet keskijohdon muutoskäytänteissä ja toimintatavoissa vaikuttavat organisaation suoriutumiseen ja muutosaloitteiden onnistumiseen. Tämän tutkimuksen tavoitteena onkin selvittää, millä eri tavoilla keskijohtajat vaikuttavat organisaation muutosprosesseihin. Tutkimuksen teoreettinen viitekehys on muodostettu määrittelemällä organisationaalinen muutos, tunnistamalla sen eri lähestymistavat, esittelemällä ja analysoimalla olemassa olevia muutosmalleja ja viitekehyksiä, tunnistamalla muutosprosessin eri vaiheet, ja lopuksi määrittelemällä keskijohdon eri roolit, vastuualueet ja tavoitteet muutosprosessin aikana. Koska tutkimus pyrkii kaventamaan kuilua alan teorian ja käytännön välillä, teoreettiset havainnot testataan empiirisen tutkimuksen avulla. Laadullista tutkimusmateriaalia kerätään haastattelemalla keskijohtajia puolistrukturoiduin teemahaastatteluin. Empiiriset tutkimustulokset analysoidaan ja peilataan edellä kuvattuun tutkimuksen teoreettisen viitekehykseen. Sekä tutkimuksen teoreettiset että empiiriset havainnot viittaavat siihen, että keskijohdon rooli muutosprosesseissa korostuu erityisesti jalkauttamisvaiheen aikana. Muutosorientoituneen johtajuuden avulla he voivat edesauttaa muutosprosessin etenemistä ja johtaa organisaatiota haluttuun suuntaan. He voivat myös omalla toiminnallaan estää mahdollista muutosvastarintaa, motivoida ihmisiä osallistumaan muutokseen ja varmistaa kehityksen jatkuvuuden. Tutkimus pyrkii tarjoamaan alan tutkijoille uusia näkemyksiä nykypäivän muutosjohtamiskäytänteistä ja siitä, miten menestyvät muutosjohtavat toimivat muutoksen eri vaiheiden aikana. Lisäksi tutkimustulokset vahvistavat omalta osaltaan alan teoriaa ja tarjoavat uusia näkemyksiä aikaisempiin tutkimustuloksiin.
Keywords: change management (leadership); middle management; change; business management; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development